Helicobacter pylori regulates stomach diseases by activating cell pathways and DNA methylation of host cells - Xi, Yue; Zhang, Xiao-Li; Luo, Qing-Xin; Gan, Hai-Ning; Liu, Yu-Shi; Shao, Shi-He; Mao, Xu-Hua (Frontiers in Cell and Developmental Biology, 2023)
One of the most prevalent malignant tumors of the digestive tract is gastric cancer（GC). Age, high salt intake, Helicobacter pylori (H. pylori) infection, and a diet deficient in fruits and vegetables are risk factors for the illness. A significant risk factor for GC is infection with H. pylori. Infecting gastric epithelial cells with virulence agents secreted by H. pylori can cause methylation of tumor genes or carcinogenic signaling pathways to be activated. regulate downstream genes' aberrant expression, albeit the precise mechanism by which this happens is unclear. Oncogene, oncosuppressor, and other gene modifications, as well as a number of different gene change types, are all directly associated to the carcinogenesis of GC. This paper detailed H. pylori and its virulence factors, as well as the activation of the NF-κB, MAPK, JAK/STAT signaling pathways, and DNA methylation following infection with host cells via virulence factors, resulting in abnormal gene expression. As a result, host-related proteins are regulated, and GC progression is influenced. This review summarizes the pertinent findings, discusses the complex signaling pathway molecular mechanisms at work, and proposes new avenues for immunotherapy of this important disease.